2015
DOI: 10.1007/s10147-015-0828-1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance policy for Japanese patients with stage I testicular germ cell cancer in the multi-detector computed tomography era

Abstract: Fewer than 10 % of Japanese patients with stage I testicular GCC suffered a recurrence in the 5-year observation period of this study. The risk of occult disease, which will result in relapse, might be decreased in the MDCT era. All patients must be fully informed of the anticipated recurrence rate and the potential risks of exposure to chemotherapy agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Yuasa et al [ 18 ] observed relapses in 14.2% of patients without risk factors after AS. In our group of CSI testicular seminoma patients managed by AS, the relapse rate was determined to be 11.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Yuasa et al [ 18 ] observed relapses in 14.2% of patients without risk factors after AS. In our group of CSI testicular seminoma patients managed by AS, the relapse rate was determined to be 11.9%.…”
Section: Discussionmentioning
confidence: 99%